Influence of the common varistor dopants (CoO, Cr2O3 and Nb2O5) on the structural properties of SnO2 ceramics - Brankovic, G.; Brankovic, Z.; Davolos, Marian Rosaly [UNESP]; Cilense, M.; Varela, José Arana [UNESP] (Elsevier B.V., 2004)
The influence of dopants commonly used in SnO2 varistor ceramics, such as CoO, Cr2O3 or Nb2O5, on the structural properties of SnO2 was investigated. Several SnO2-based ceramics containing only one of the dopants were prepared and characterized. Spectroscopic investigations [visible, near infrared (IR) and IR region] were performed to obtain information about dopants valence states inside the ceramics, as well as about their influence on electronic structure of the material. Structural properties were investigated by X-ray diffraction analysis and mechanisms of dopant incorporation were proposed. Obtained results were confirmed with results of the electrical measurements. Microstructural changes in doped ceramics were investigated by scanning electron microscopy (SEM) analysis that showed great differences in densities, grain size, and morphology of the SnO2 ceramics depending on type of dopants and their distribution. (C) 2004 Published by Elsevier B.V.
Keywords: ceramics; infrared (IR) spectroscopy; energy dispersive X-ray analysis (EDS); scanning electron microscopy (SEM)